The development of a system of European regional purchasing power parities - Ben Gardiner; Saxon Brettell (European Regional Science Association (ERSA), 2002)
This paper discusses ways in which a system of Purchasing Power Parities defined at the NUTS-2 regional disaggregation could be developed, and what the implications could be for EU policy, particularly the evaluation of Structural Funds and the conclusions made thus far about regional convergence and development. Currently regional GDP in current prices is deflated using national purchasing power indices, mostly only derived from surveys undertaken in the capital cities of the Member States. For some Member States, the national PPP are corrected for price differences within the country, using spatial correction factors for individual price surveys, given these factors are provided by the countries. Clearly, therefore, for the majority of the countries, these estimates of regional GDP do not take any account of significant differences in cost of living within countries. This paper draws on the preliminary results of a research project being undertaken for Eurostat to examine options for deriving a system of regional prices. Much research has already been published at the level of international prices, partly through the International Comparison Programme (ICP), but little work has been carried out on inter-regional differences. The paper reviews briefly the theoretical and empirical literature on national PPPs. It then discusses key conceptual issues, including the problem of the difference between expenditure-based measures (used for national PPPs) versus the output-based procedure used to estimate regional GDP. A review of what data currently exists to inform estimates, particularly the detailed tables of consumer price indices (CPI), is followed by proposals for how a system of regional PPPs might be developed. This paper concludes with an examination of the potential implications of the work, how it could affect regional policy in the future and conclusions already made about regional development. Some stylised examples are used to show how adopting regional versus national prices could affect the results.
Keywords: 330